A Cost-side Analysis on Collusive Sustainability - Luca Lambertini; Dan Sasaki (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
In an oligopoly supergame, firm`s actions in prices and quantities are subject to non-negativity constraints. These aonstarints can obstruct the practicability of oprimal punishment (a la Abreu (1989), Lambson (1987), and Hacker (1996)) in sustaining tacit collusion. Noting that the prospect of single-period optimal punichment depends indispensably upon firms` ability to charge prices strictly below marginal costs (loss-making pricing), under the presence of positive rice constraints, marginal costs can serve as a "fudge" to materialize single-period optimal punishment. In this pa-per we charactarise the effects of profit-cost ratios (or mark-ups) on the sustainability of tacit col-lusion, in light of optimal punishment.
Keywords: 330